Spectrum and frequencies of mutations in the MFN2 gene and its phenotypical expression in Czech hereditary motor and sensory neuropathy type II patients - Brožková, Dana Šafka; Posádka, Jan; Laššuthová, Petra; Mazanec, Radim; Haberlová, Jana; Sišková, Dana; Sakmaryová, Iva; Neupauerová, Jana; Seeman, Pavel (Molecular medicine reports, 2013)
The axonal type of Charcot‑Marie‑Tooth (CMT) disorders is genetically heterogeneous, therefore the causal mutation is unlikely to be observed, even in clinically well characterized patients. Mitofusin‑2 (MFN2) gene mutations are the most frequent cause of axonal CMT disorders in a number of populations. There are two phenotypes; early onset, which is severe and late onset, which is a milder phenotype. A cohort of 139 unrelated Czech patients with axonal neuropathy was selected for sequencing and multiplex ligation-dependent probe amplification analysis (MLPA) testing of the MFN2 gene. A total of 11 MFN2 mutations were detected, with eight pathogenic mutations and three potentially rare benign polymorphisms. MLPA testing in 64 unrelated patients did not detect any exon duplication or deletion. The frequency of the pathogenic mutations detected in Czech hereditary motor and sensory neuropathy type II (HMSN II) patients was 7.2%. Early onset was more frequent among pathogenic mutation cases. Therefore we propose to examine the MFN2 gene mainly in patients with early and severe axonal CMT.
Keywords: Mutation Rate; Polymorphism, Single Nucleotide; exony; rodina; Humans; Family; mutační rychlost; jednonukleotidový polymorfismus; mutace; Phenotype; Exons; lidé; Mitochondrial Proteins; mitochondriální proteiny; Charcotova-Marieova-Toothova nemoc; GTP-fosfohydrolasy; fenotyp; Charcot-Marie-Tooth Disease; Czech Republic; Mutation; Česká republika; GTP Phosphohydrolases